Lipase Activity, Hematological and Blood Biochemistry of Osphronemus gouramy Fed with Suplementation of Spirulina platensis and Chlorella vulgaris - Sorta Basar Ida Simanjuntak; Hana Hana; Riska Yunida; Maditaningtyas Hawwa Zuwanda (Universitas Jenderal Soedirman, 2022)
Spirulina platensis and Chlorella vulgaris are algae that contain high nutrients, such as protein, vitamins, and minerals. The purpose of this study was to determine the lipase activity, hematological, blood biochemistry and to obtain the most effective supplementation of Spirulina platensis and Chlorella vulgaris in feed to enhance lipase activity, hematological parameter, blood biochemistry of gourami. The study was conducted experimentally in which 100 gourami fish were assigned randomely to the following treatments: P1 = Spirulina platensis 6 g kg-1 feed; P2 = Chlorella vulgaris 4 g kg-1; P3 = Spirulina platensis 3 g kg-1 + Chlorella vulgaris 2 g kg-1; P4 = Spirulina platensis 2 g kg-1 + Chlorella vulgaris 3 g kg-1; and C = feed without supplementation as control, in four replicates. Lipase activity was measured in various digestive organs at pH 2, 5, 7, 8 and 10. The results showed that supplementation of Spirulina platensis and Chlorella vulgaris affected lipase activity; hematological parameter and blood biochemistry of gourami. The combination Spirulina platensis + Chlorella vulgaris supplementation in feed showed the highest increased of the lipase activity, hematological parameter and blood biochemistry of gourami. Spirulina platensis + Chlorella vulgaris supplementation in feed might improve growth and immunity since the increase of digestive enzyme functioning which enhances feed utilization and the increase of biochemical parameters of blood, respectively.